Perlindungan Hukum Bagi Nasabah Asuransi Kesehatan Berdasarkan Undang-Undang No.40 Tahun 2014 - Novita, Tri Reni; Husna, M. Faisal; Ovami, Debbi Chyntia (Universitas Ekasakti, 2023)
The Indonesian state continues to pay attention to the welfare of its people, especially health, which is part of human rights. This is stated in article 28 H paragraph (1) of the 1945 Contitution which state ; Everyone has the right to live a good and healthy services. Specifically regarding legal protection for health insurance policy holders, it is regulated in the Law of the Republic of Indonesia Number 20 of 2014 concerning Indurance. Health insurance claims in the form of claims from the insured aas the insurance policy holder. Teha insurance company or the insurer must make patments to the policyholder or the insured when making an insurance claim, this is a benefit of the health insurance they have. Health insurance is a financing system that provides social insurance in lieu of facing risks caused bya health users (illness), both diseases that can be cured on an outpatient care. This of course requires very high costs for a class of middle and lower economic people. Having health insurance is part of the risk management system, because when there is a disaster or illness, the policyholder does not need to think about the cost of treatment. The cost of this treatmen can be covered from insurance claims that are owned